Multicomponent reactions in the discovery of organocatalysts and the diversification of organocatalytic approaches - De La Torre, Alexander Fernández (Universidade Federal de São Carlos, 2015)
This thesis reports the development of multicomponent approaches directed to specific objectives: a) the discovery of new and efficient peptide-based catalyst for asymmetric transformations and b) the synthesis of (hetero)cyclic natural products-like compounds derived from organocatylic/multicomponent reaction sequences. Chapter 1 describes the utilization of the Ugi-4CR reaction for the development of new prolyl pseudo-peptides capable to act as aminocatalysts in asymmetric conjugate addition reactions. Thus, a series of pseudo-peptides having the generic sequences Pro-N-R1-AA-NHR3, being AA an amino acid and R1 and R3 either alkyl or amino acids, were obtained in moderate to excellent yields. The prolyl pseudo-peptides were screened for their catalytic efficacy, most of them proving great efficiency and good to excellent enantio- and diastereoselectivity in the asymmetric conjugate addition of aldehydes to nitroolefins. However, only moderate results were obtained in the asymmetric organocatalytic aldol reaction. A molecular modeling and NMR study were performed for catalysts 67 and 69, aiming to understand their different organocatalytic behavior based on the conformational features. A similar multicomponent process followed by a polymerization step was developed to obtain two new polyfurfuryl alcohol polymers bearing the prolyl pseudo-peptide motif anchored to polymer chain. The prolyl peptide-containing polymers were utilized in the heterogeneous organocatalytic conjugate addition of aldehydes to nitroolefins under bath and flow conditions, producing Michael adducts in moderate yield and enantioselectivity but in excellent diastereoselectivity. Chapter 2 describes the development of new reaction sequences based on consecutive organocatalytic and multicomponent reactions. Several aminocatalytic conjugate addition procedures were implemented to prepare chiral hemiacetals, which were next used in varied Ugi-type multicomponent reactions. These sequences include: a) the Michael addition of nitroethanol to , -unsaturated aldehydes followed by an Ugi reaction leading to cyclic depsipeptide mimics; b) the Michael addition of 1,3-cycloalkanediones to , -unsaturated aldehydes followed by a new stereoselective Ugi-Smiles-type reaction leading to hexahydroquinolin-6-ones; and c) the Michael addition of aldehydes to phenolic nitroolefins followed a new type of multicomponent reaction, leading to pentasubstituted cyclopentenes. The success of these sequences proved the potential of combining organocatalytic asymmetric transformations with follow-up multicomponent reactions for accessing natural product-like cyclic compounds.
Multicomponent reactions in the discovery of organocatalysts and the diversification of organocatalytic approaches
Keywords: Química orgânica; Estéreoseletividade; Reações multicomponentes; Organocatalises; CIENCIAS EXATAS E DA TERRA::QUIMICA